The roles of the Shariah committee in the implementation of value-based intermediation - Hassan, Rusni; Hasan, Aznan; Itam@Ismail, Muhammad Issyam (REDmoney Group, 2018)
As part of the eff ort to stimulate new growth in Malaysia’s Islamic fi nance industry, Bank Negara Malaysia issued the Strategy Paper on Value-Based Intermediation (VBI) which provides strategies to strengthen the roles and impact of Islamic banking institutions toward providing positive and sustainable values to the economy, community and environment. Islamic banking institutions are expected to take proactive action in adopting the VBI initiatives in their operation and business activities. The Shariah committ ee plays a vital role in ensuring that the directions taken by Islamic banking institutions in adopting the VBI initiatives are consistent with Shariah principles. The implementation of VBI will be a good platform for the Shariah committ ee to play its role in leading Islamic banking institutions toward achieving the objectives of Shariah in Islamic fi nance.